Hubungan Antara Paritas dengan Kejadian Perdarahan Post Partum - M. Arief Rachman Adi Pradana; M.Rafli Febri Asshiddiq (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Background: Postpartum hemorrhage is defined as bleeding that occurs immediately after delivery (delivery), bleeding that exceeds 500 ml. The aim of the study was the relationship between parity and the incidence of postpartum hemorrhage. Methods: using literature studies from national and international journals by summarizing the discussion topics and comparing the results presented in the articles. Results: There is a parity relationship with the incidence of postpartum hemorrhage. Primiparity is a risk factor for postpartum hemorrhage due to the lack of information obtained by the mother, causing unpreparedness to face possible complications in pregnancy and childbirth. Parity 3 is one of the factors causing postpartum hemorrhage due to weakening of uterine contractions due to excessive stretching of the uterine muscles, causing thinning of the uterine wall. Conclusion: There is a parity relationship with the incidence of postpartum hemorrhage.